Intervenção no sistema de espaços livres do Porto de Manaus: requalificação do patrimônio edificado e da paisagem no Centro Antigo. - Silva, Victoria Alves da (Brasil, 2023)
This dissertation presents the Public Port of Manaus in its historical, architectural, spatial and patrimonial essence. In order to discuss its inherent value in the city’s image and memory, we will evidence the Port’s public and historic role as an urban instrument and how this is currently presented through an analysis of its potential, existing structure and the relationships between Manaus’ Historic Center users and passersby. Thus, through understanding the implementation of the Public Port, its historical and contemporary use, the typologies of waterway terminals and waterfronts, and also the analysis of referenced projects, it will be proposed a requalification of the landscape, allied to improving and continuing port activities and creating a closer relationships between the people of Manaus, the public space and the banks of Rio Negro.